Environmental Sustainability: Sustainable Development Goals and Human Rights - Seixas, Sonia Regina da Cal; Hoefel, João Luiz de Moraes (AAP research notes on optimization and decision-making theories, 2021)
United Nations 2030 Agenda for Sustainable Development 17 Goals blends the three dimensions of sustainable development: economic, social and environmental. They function as commitments to be met by governments, civil society and the private sector for a 2030 collaborative project. The five keywords to achieve it are: People, Planet, Prosperity, Peace, and Partnerships. Another reading is to link these precepts with the Universal Declaration of Human Rights because to obtain real development we need full realization of human rights. This book analyses Sustainable Development considering Sustainable Development Goals, their importance concerning human rights and its significance for a Sustainable Society.